2021
DOI: 10.1002/mds.28497
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity Markers in Parkinsonian Subthalamic Single‐Unit Activity

Abstract: Background: Impulsive-compulsive behaviors are common in Parkinson's disease (PD) patients. However, the basal ganglia dysfunctions associated with high impulsivity have not been fully characterized. The objective of this study was to identify the features associated with impulsive-compulsive behaviors in single neurons of the subthalamic nucleus (STN). Methods: We compared temporal and spectral features of 412 subthalamic neurons from 12 PD patients with impulsive-compulsive behaviors and 330 neurons from 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
(50 reference statements)
0
17
0
Order By: Relevance
“…The difference is relevant to the extent that it supports a significant discrimination of the two conditions patient‐wise. We previously found that firing regularity was among the markers of ICB+ condition 13 . The novel analysis presented in this manuscript shows that the difference between conditions is localized in the ventral part.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…The difference is relevant to the extent that it supports a significant discrimination of the two conditions patient‐wise. We previously found that firing regularity was among the markers of ICB+ condition 13 . The novel analysis presented in this manuscript shows that the difference between conditions is localized in the ventral part.…”
Section: Discussionmentioning
confidence: 54%
“…Microelectrode recording (MER) studies on STN single neuron activity showed a relationship with decision‐making and ICB 12 but did not investigate how this relationship varied within the STN. Recently, we observed in PD ICB subjects in drugs OFF condition a significant reduction in standard PD markers in STN single unit activity such as beta oscillations and burstiness 13 . Here, we investigate whether this ICB‐specific feature can be associated to a specific location within STN.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations